Reducing Blood Pressure and Pulse Rate in Hypertension Patients Using Hatha Yoga - Keloay, Maitha Annthonette Wulan; Efendi, Ferry; Makhfudli, Makhfudli (Indonesian Journal of Global Health Research, 2024)
Several factors that can influence blood pressure and heart rate in hypertensive patients are physical activity, where hatha yoga can be a non-pharmacological intervention solution for hypertensive sufferers by emphasizing the effects of relaxation and blood circulation. The aim of this study was to analyze the effect of hatha yoga practice on reducing blood pressure and pulse rate in patients with hypertension. Methods: This research uses a quasi-experiment design with a pre-post test control group design. The research population was 72 elderly people with hypertension and 48 respondents were recruited as samples using purposive sampling techniques. This research was divided into 2 groups, namely the treatment group and the control group, each with 24 respondents. The independent variable hatha yoga was carried out using standard operating procedures (SOP), while blood pressure and pulse were the dependent variables measured using a sipgnomanometer, stethoscope, oximeter and observation sheet. Data analysis used a paired t-test with p<0.05 and because the data was normally distributed. Results: There was an effect of hatha yoga on blood pressure and pulse rate in hypertensive patients (p=0.000) in the intervention group. Systolic blood pressure decreased from 147.78 ± 6.014 to 131.08 ± 6.576. Diastolic blood pressure decreased from 95.08 ± 2.278 to 80.81 ± 6.032 and pulse rate decreased from 87.62 ± 5.570 to 79.49 ± 5.295. Conclusion: Non-pharmacological intervention using hatha yoga shows a positive influence in reducing blood pressure and pulse rate in elderly people with hypertension.